(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Anita Desai does not manage such issues which are absolutely the domain of a feminist scholar. There lies a more profound refinement between feminine sensibility and feminist approach. The novelist taking a shot at the feminine sensibility does not dither to stick point the equivalent obligation of female characters. While a feminist (mastermind taking a shot at the western situated feminism) tries to see just the concealment, mistreatment, brutalities and shameful acts did to the woman kind before and he interfaces these wonders with the present. Desai does not take after this sort of belief system in her fictional world.